Is output performance all about the resources? a fuzzy- set qualitative comparative analysis of street- level bureaucrats in Switzerland - Thomann, Eva (2015)
This article refines Lipsky's assertion that lacking resources negatively affects output performance. It uses fuzzy-set Qualitative Comparative Analysis to analyse the nuanced interplay of contextual and individual determinants of the output performance of veterinary inspectors as street-level bureaucrats in Switzerland. Moving beyond Lipsky, the study builds on recent theoretical contributions and a systematic comparison across organizational contexts. Against a widespread assumption, output performance is not all about resources. The impact of perceived available resources hinges on caseloads, which prove to be more decisive. These contextual factors interact with individual attitudes emerging from diverse public accountabilities. The results contextualize the often-emphasized importance of worker client interaction. In a setting where clients cannot escape the interaction, street-level bureaucrats are not primarily held accountable by them. Studies of output performance should thus consider gaps between what is being demanded of and offered to street-level bureaucrats, and the latter's multiple embeddedness. - Reproduced.
Keywords: Civil service - Switzerland; Civil service